Multiple sclerosis and pregnancy as a significant social problem in modern neurology - Kamieniak, Maciej; Wolanin, Natalia; Marzęda, Magdalena; Jarosz, Piotr; Kobiałka, Izabela; Blicharz, Agnieszka; Swatko, Tomasz (Journal of Education, Health and Sport, 2022)
Along with the increasing number of reported cases, multiple sclerosis, one of the main causes of disability among young adults, is nowadays an increasingly common health problem. Considering the fact that it occurs mainly between 20 and 40 years and affects women more often, the question of the impact of the disease on pregnancy becomes obvious. In view of the wide selection of drugs for various purposes and often highly individualized forms of therapy, it seems also important to determine the safety profile of these agents in relation to the health of the pregnant woman and the fetus. All of this is a significant challenge for neurologists and obstetricians and is the subject of many research and studies. The awareness of society, especially women, in the face of the growing problem seems to be equally important. This paper summarizes the current state of knowledge on these issues.